Increased oxidative stress, inflammation and fibrosis in perirenal adipose tissue of patients with cortisol-producing adenoma. (2nd January 2019) - Wu, Chunyan; Zhang, Huijian; Zhang, Jiajun; Zhang, Hongbin; Zeng, Yanmei; Fang, Shu; Li, Ping; Zhang, Yudan; Lin, Xiaochun; Wang, Ling; Xue, Yaoming; Guan, Meiping
ABSTRACT: Although much is known about that corticosteroids affect the functions of adipose tissues, little genetic information is available for perirenal adipose tissue (peri-N) from patients with cortisol-producing adenoma (CPA). We conducted microarray analysis of peri-N from patients with CPA by using an Affymetrix human U133 plus 2.0 array. We also analysed the inflammation, fibrosis and oxidative stress in vitro. Compared with normotension (NT) group, CPA group has significantly higher protein levels of TNFα, IL-6, fibronectin (FN) and collagen I (COLI). The protein level of NADPH oxidase 4 (Nox4) significantly increased, while nuclear factor erythroid 2-related factor 2 (Nrf2) and hemeoxygenase-1 (HO-1) levels were significantly reduced in the CPA group. Dexamethasone markedly induced fibrosis and adipogenesis-related gene expression in predifferentiated stromal vascular fraction (SVF) cells, 3T3-L1 preadipocytes and brown preadipocytes. Chronic exposure to endogenous glucocorticoids due to CPA increases peri-N oxidative stress, inflammation and fibrosis, which may contribute to the metabolic disturbances associated with hypercortisolism in these patients.